The Problem of Human in Islam - Mikailova, Narmina (Scholarya Demo Journal of Ruby, 2019)
Islam revives in the present day as a part of the global culture. The adventof Islam is closely connected with the fundamental changes in the moraldevelopment of mankind. This religion is still regarded as the source of socialand cultural values and determines the progress of culture in large areas.Nowadays Muslim states support the idea of establishing the Muslim religiouscommunity as a political regulatory unit. Total submission to the God’s will isthe major dogmatic and moral doctrine of the Quran.In Islamic philosophy, human is a synthesis of spirituality and materiality.Spirit is the cognitive subject. Knowledge is percieved as the result ofphysical and mental vision. Moral freedom is determined by cosmic order. The activity of Eastern peripatetics is concerned with the formation ofrationalist doctrines on human activity. Human is regarded as a microcosmos,reflecting the nature of Universe.Human mental nature is based on cognitive process. The essence of humannature is characterized by intelligence and reason. Activity of intelligence is themost useful one for humans and determine the happinness of human life.